Internalisasi Nilai Pendidikan Melalui Lomba 17 Agustus Di Jenjang Aliyah Pesantren Tahfidz Ibnu Aqil - Andriani, Andriani; Qorib, Muhammad (EL-EMIR Institute, 2025)
The celebration of Indonesia’s Independence Day on August 17th is not only a historical commemoration but also holds potential as a character education medium within pesantren environments. This study aims to examine how the implementation of Independence Day competitions at the Aliyah level of Pesantren Tahfizh Ibnu Aqil serves as a means of internalizing educational values among students. The competitions include quiz contests, ranking 1 contests, proclamation text reading, national and regional song choir, classroom decoration, and bulletin board contests all designed to be educational and contextually relevant. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation throughout the activities. The results show that these competitions effectively foster essential character values such as nationalism, cooperation, responsibility, discipline, creativity, and enthusiasm for learning. The active participation of 111 students across six Aliyah classes demonstrates that these activities holistically and sustainably shape the students’ character.